2017
DOI: 10.1089/chi.2017.0047
|View full text |Cite
|
Sign up to set email alerts
|

Step Tracking with Goals Increases Children's Weight Loss in Behavioral Intervention

Abstract: Providing children with pedometers and individualized step goals was an effective approach to produce weight loss. Further work is needed to increase the strength of interventions to achieve clinically meaningful weight reduction for children with obesity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 31 publications
1
19
0
Order By: Relevance
“…This result is consistent with previous research [16,17] indicating that QOL improves with increased physical activity. One study using step-tracking in a majority-black sample of children showed a positive relationship between steps taken and health-related QOL [28]. A cross-sectional study in low-income children found that depression moderated the relationship between physical activity and QOL such that physical activity was not related to QOL in children with more depressive symptoms [20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This result is consistent with previous research [16,17] indicating that QOL improves with increased physical activity. One study using step-tracking in a majority-black sample of children showed a positive relationship between steps taken and health-related QOL [28]. A cross-sectional study in low-income children found that depression moderated the relationship between physical activity and QOL such that physical activity was not related to QOL in children with more depressive symptoms [20].…”
Section: Discussionmentioning
confidence: 99%
“…An exercise intervention did not improve global self-worth in black children who were overweight, though it did in white peers [22]. Benefits of physical activity on QOL, depression, and self-worth may be less evident in black children than their white peers [22,24,25,28,29]. There is scant literature relating physical activity to QOL and other psychological factors, especially in children who are overweight, obese, or black.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies of weight management interventions have shown that children can successfully increase their step count from baseline as part of an intervention. 68 Yet these studies fail to consistently demonstrate a significant change in BMI percentile from controlled conditions. 68 , 69 Staiano et al were able to demonstate weight loss in groups of children issued pedometers as part of a 10-week, family-based weight management intervention which included physical activity, nutrition, and behavior modification (as well as money compensation).…”
Section: Impacting Habitual Dynamicsmentioning
confidence: 92%
“… 68 , 69 Staiano et al were able to demonstate weight loss in groups of children issued pedometers as part of a 10-week, family-based weight management intervention which included physical activity, nutrition, and behavior modification (as well as money compensation). 68 Those in the group issued pedometers and a step count goal increased their daily step count, as well as reduced their BMI and BMI z score significantly more than those issued a pedometer without a step goal count. Both groups saw a reduction in BMI and an increase in step count from baseline.…”
Section: Impacting Habitual Dynamicsmentioning
confidence: 99%
“…Physical activity provides a cascade of health benefits especially needed for adolescents with obesity, including chronic disease prevention and improved cardiometabolic health, quality of sleep, improved executive functioning, and reduced risk of depression and anxiety, among others (2018 Physical Activity Guidelines Advisory Committee, 2018). Physical activity may also be a means by which adolescents with obesity can improve their subjective health including their body satisfaction, perceived physical conditioning, and perceived physical self-worth (Goldfield et al, 2007), as well as their health-related quality of life (Staiano et al, 2017a). Identifying enjoyable options for physical activity may therefore be a mechanism to not only promote sustained physical activity but also improve psychosocial health among adolescents with obesity.…”
Section: Introductionmentioning
confidence: 99%